1995
DOI: 10.1007/bf00299164
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy for management of nontraumatic acute abdomen

Abstract: The diagnostic and therapeutic influence of laparoscopy has been studied in 255 patients presenting with nontraumatic acute abdominal pain. Laparoscopy provided a correct diagnosis in 93% (236 of 255) of the cases, the others requiring a laparotomy. An erroneous preoperative diagnosis was corrected by laparoscopy in 50 patients (20%), which called for a change of treatment in 25 patients (10%). Seventy-three percent (186 of 255) of acute abdominal conditions were treated exclusively by laparoscopy, 23% (58 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
2
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 14 publications
(16 reference statements)
3
28
2
7
Order By: Relevance
“…In selected patient populations where no prior diagnostic imaging has been performed, a diagnostic laparoscopy can accurately diagnose the cause of the abdominal pain in 80 - 94% of patients ((EL B) [33,34,35,36,37]). Postoperative complications have been reported in 3.5 - 25% of patients after diagnostic laparoscopy ((EL B) [33,34,36,37]) (online suppl. appendix 2, table 2.8).…”
Section: Resultsmentioning
confidence: 99%
“…In selected patient populations where no prior diagnostic imaging has been performed, a diagnostic laparoscopy can accurately diagnose the cause of the abdominal pain in 80 - 94% of patients ((EL B) [33,34,35,36,37]). Postoperative complications have been reported in 3.5 - 25% of patients after diagnostic laparoscopy ((EL B) [33,34,36,37]) (online suppl. appendix 2, table 2.8).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated a high diagnostic accuracy for DL (70-99%; levels 1-3 evidence) [2][3][4][5][6][7][8][9][10][11][12][13][14]. A randomized trial for acute nonspecific abdominal pain by Decadt et al [2] showed that the application of early DL significantly improved diagnostic accuracy compared with an observation group (81% vs 36%; p\0.001).…”
mentioning
confidence: 97%
“…Findings have shown that DL changes the treatment strategy for 10% to 58% of patients with acute nonspecific abdominal pain (levels 2 and 3 evidence) [4][5][6][7][8][9][10]. Although computed tomography (CT) of the abdomen and pelvis was scarcely used during the preoperative workup in the majority of published studies reviewed, one study demonstrated a higher diagnostic accuracy with DL in the diagnosis of diverticulitis than with CT of the abdomen or colonic contrast enema (level 2 evidence) [14].…”
mentioning
confidence: 99%
“…Although a number of studies [1,4,14] have described laparoscopic surgery used in nontrauma emergencies other than acute cholecystitis, it is clear that more experience and collective data are needed.…”
mentioning
confidence: 99%